Determination of the relationship between core endurance and isokinetic muscle strength of elite athletes - Kocahan, T.; Akinoglu, B. (Journal of Exercise Rehabilitation, 2018)
Muscle strength and core endurance are both factors contributing to athletes' performance and prevalence of injuries. There are no studies indicating the relationship between muscle strength around the shoulder and knee joints and core endurance. The aim of our study is to determine the relationship between core endurance and isokinetic muscle strength of knees and shoulders of elite athletes. Seventy-one elite athletes (weight lifting, boxing, taekwondo, biathlon, and ice skating) (age, 18.13±2.9 years) were included in the study. Isokinetic muscle strength of shoulder internal-external rotation and knee flexion-extension were determined by using an Isomed 2000 device. Core endurance of athletes was assessed using the Mcgill Core Endurance Tests. There was a relationship between the shoulder internal rotation and external rotation peak torque/body weight (PT/W) and all endurance tests except extension endurance tests. There was also a relationship between knee flexion PT/W and all core endurance tests. While there was a relationship between knee extension PT/W and extension endurance and the lateral bridge test, this relationship was not found with the flexor endurance test. These results indicate that the upper and lower extremity muscle strength and core endurance of athletes are related with each other and must be evaluated and trained as a whole with each other.